Training of students at the department of obstetrics and gynecologyunder conditions of the state of martial law - Siusiuka, V. H.; Onopchenko, S. P.; Shevchenko, A. O.; Deinichenko, O. V.; Kolokot, N. H.; Сюсюка, Володимир Григорович; Онопченко, Світлана Павлівна; Шевченко, Анна Олександрівна; Дейніченко, Олена Валеріївна; Колокот, Наталя Григорівна (Berlin : International Science Group, 2024)
The realities of modern life require the development of various methods of distance learning in higher medical educational institutions, the introduction of the latest information technologies into the educational process.